Noninvasive Risk Stratification After HCV Eradication in Patients With Advanced Chronic Liver Disease. Issue 4 (16th March 2021) - Semmler, Georg; Binter, Teresa; Kozbial, Karin; Schwabl, Philipp; Hametner‐Schreil, Stefanie; Zanetto, Alberto; Gavasso, Sabrina; Chromy, David; Bauer, David J.M.; Simbrunner, Benedikt; Scheiner, Bernhard; Bucsics, Theresa; et al.
Abstract : Background and Aims: Risk stratification after cure from hepatitis C virus (HCV) infection remains a clinical challenge. We investigated the predictive value of noninvasive surrogates of portal hypertension (liver stiffness measurement [LSM] by vibration‐controlled transient elastography and von Willebrand factor/platelet count ratio [VITRO]) for development of hepatic decompensation and hepatocellular carcinoma in patients with pretreatment advanced chronic liver disease (ACLD) who achieved HCV cure. Approach and Results: A total of 276 patients with pretreatment ACLD and information on pretreatment and posttreatment follow‐up (FU)‐LSM and FU‐VITRO were followed for a median of 36.6 months after the end of interferon‐free therapy. FU‐LSM (area under the receiver operating characteristic curve [AUROC]: 0.875 [95% confidence interval [CI]: 0.796‐0.954]) and FU‐VITRO (AUROC: 0.925 [95% CI: 0.874‐0.977]) showed an excellent predictive performance for hepatic decompensation. Both parameters provided incremental information and were significantly associated with hepatic decompensation in adjusted models. A previously proposed combined approach (FU‐LSM < 12.4 kPa and/or FU‐VITRO < 0.95) to rule out clinically significant portal hypertension (CSPH, hepatic venous pressure gradient ≥10 mm Hg) at FU assigned most (57.3%) of the patients to the low‐risk group; none of these patients developed hepatic decompensation. In contrast, in patients in whom FU‐CSPH was ruled in (FU‐LSM > 25.3 kPa and/or FU‐VITRO > 3.3; 25.0% of patients), the risk of hepatic decompensation at 3 years following treatment was high (17.4%). Patients within the diagnostic gray‐zone for FU‐CSPH (17.8% of patients) had a very low risk of hepatic decompensation during FU (2.6%). The prognostic value of this algorithm was validated in an internal (n = 86) and external (n = 162) cohort. Conclusion: FU‐LSM/FU‐VITRO are strongly and independently predictive of posttreatment hepatic decompensation in HCV‐induced ACLD. An algorithm combining these noninvasive markers not only rules in or rules out FU‐CSPH, but also identifies populations at negligible versus high risk for hepatic decompensation. FU‐LSM/FU‐VITRO are readily accessible and enable risk stratification after sustained virological response, and thus facilitate personalized management.